INTERCULTURAL COMMUNICATION AS MAIN FACTOR IN FORMING OF ENGINEERING SPECIALISMS STUDENTS COMMUNICATIVE COMPETENCE - Tupchenko, V. (Problems of Engineer-Pedagogical Education, 2021)
The article is devoted to the study of the problem of communicative competence formation of engineering specialisms students in the process of intercultural communication. It is well known that the basis for the development of the modern civilized world is the diversity of cultures. Researches pay great attention to the study of the idea of the importance of language in cognitive process. An important tool of intercultural educational resource is the process of active intercultural communication by means of a foreign language. The article describes the theoretical aspect of the problem, it is revealed that modern stage of communicative competence formation provides intercultural competence development of students. The article analyzes the concept of «intercultural communicative competence» which is defined as an integral, multi-level personal and professional quality which is a combination of knowledge, judgments, value attitudes, determined by the aims and objectives of intercultural communication in higher education institutions on the basis of mutual understanding, mutual respect and tolerance. The article examines certain directions of the formation of students communicative competence in the process of studying a foreign language of professional orientation, outlines principles and approaches on which communicative competence formation in the process of intercultural communication is based. According to the purpose of this paper the context of intercultural communication, its principles and approaches which form the basis for communicative competence formation of engineering specialisms students are determined, and the role of intercultural communication in this process is analyzed. The author considers the problem of intercultural communication development in the engineering specialisms students during foreign languages classes. The research is based on the set of rules and procedures that contain mixed methods, including integration of study of both quantitative and qualitative indicators. The result of this work is conclusion that intercultural communication has interdisciplinary nature and it is determined that in the professional training of future engineering specialists intercultural communication is an integral component and the main factor in communicative competence formation. The article proposes the most effective techniques and means of communicative competence formation of engineering specialisms students in the process of intercultural communication.